How to read water clues & patterns from puddles to the sea - Gooley, Tristan 1973- (hodder press, 2025)
In How To Read Water, Natural Navigator Tristan Gooley shares knowledge, skills, tips and useful observations to help you enjoy the landscape around you. Includes over 700 clues, signs and patterns to reveal the secrets of ponds, puddles, rivers, oceans and more
First published: 2016
Keywords: Bodies of water; Nature / Psychological aspects; Nature; Water; Hydrology; Eaux; Nature / Aspect psychologique; Eau; Hydrologie; bodies of water (natural); aquatic; water (inorganic material); Popular Science; Popular Science and Mathematics